2020
DOI: 10.1128/jvi.00089-20
|View full text |Cite
|
Sign up to set email alerts
|

T Cell Responses Induced by Attenuated Flavivirus Vaccination Are Specific and Show Limited Cross-Reactivity with Other Flavivirus Species

Abstract: Members of the flavivirus genus share a high level of sequence similarity and often circulate in the same geographical regions. However, whether T cells induced by one viral species cross-react with other related flaviviruses has not been globally addressed. In this study, we tested pools of epitopes derived from dengue (DENV), Zika (ZIKV), Japanese encephalitis (JEV), West Nile (WNV), and yellow fever (YFV) viruses by intracellular cytokine staining (ICS) using peripheral blood mononuclear cells (PBMCs) of in… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 54 publications
(56 citation statements)
references
References 61 publications
5
51
0
Order By: Relevance
“…The difference in the abundance of CD4 + versus CD8 + cross-reactive memory T cells likely reflects the basic differences in antigen recognition between these T cell types. In a study examining T cell responses to different flavivirus species, it was found that cross-reactivity for CD8 + T cells was limited to peptides carrying one or two substitutions, whereas cross-reactivity for CD4 + T cells could be detected for peptides with far lower degrees of homology 19 . In sum, the cross-reactive immune memory to SARS-CoV-2 appears limited largely to one of the three major arms of adaptive immunity, the 'helper' or CD4 + T cells.…”
mentioning
confidence: 99%
“…The difference in the abundance of CD4 + versus CD8 + cross-reactive memory T cells likely reflects the basic differences in antigen recognition between these T cell types. In a study examining T cell responses to different flavivirus species, it was found that cross-reactivity for CD8 + T cells was limited to peptides carrying one or two substitutions, whereas cross-reactivity for CD4 + T cells could be detected for peptides with far lower degrees of homology 19 . In sum, the cross-reactive immune memory to SARS-CoV-2 appears limited largely to one of the three major arms of adaptive immunity, the 'helper' or CD4 + T cells.…”
mentioning
confidence: 99%
“…The CMV MP is a pool of previously reported Class I and Class II epitopes ( 43 ). To study T cell responses against SARS-CoV-2, we used the entire SARS-CoV-2 genome (GenBank: MN908947 ) and we generated a MP of 15-mer peptides (overlapping by 10 amino acids) spanning the entire sequence of the spike protein and a MP for the remainder genome consistent of dominant HLA Class II predicted CD4 + T cell epitopes as previously described ( 44 , 69 ). ( Supplementary Table 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the analysis of PBMCs isolated from individuals infected by DENV or vaccinated with DENV TV005 or YF17D vaccines, and pulsed with a pool of antigens from autologous and heterologous flaviviruses, indicated that both CD4 and CD8 T-cell responses were specific, with little or no cross-reactivity, despite the high level of homology ( 183 ). Individuals pre-exposed to DENV infection developed T-cell responses against non-structural ZIKA proteins rather than structural envelope protein, suggesting that previous flaviviral infections biased the T-cell response toward more cross-reactive non-structural epitopes ( 184 ).…”
Section: Vaccine Hurdles: Flavivirus Cross-reactivity and Antibody-dementioning
confidence: 99%